Students' English Skills and Their Ways of Learning - Atmowardoyo, Haryanto; Sakkir, Geminastiti; Sakkir, Rini Isnaeni (Celebes Journal of Language Studies, 2023)
at the Faculty of Languages and Literature, Makassar State University. The subjects of this research were fourth-semester students of the English Education Study Program, Department of English, because in that semester there were Learning and Teaching courses. This research wants to see what the student's language learning model is. Students in the fourth semester of the 2021/2022 academic year who took this course in 5 classes consisted of 210 students. However, this research was only carried out in 2 (two) classes, namely classes D and E with a total of 82 students. This research uses a qualitative approach, namely Qualitative Descriptive research. The results of this research show that Students' English language skills are obtained a little differently with only 2 (two) ways of learning English, namely formal and informal, Students' ways of learning English are slightly varied and utilize technology, including: Watching English films/videos; Listening to English songs; YouTube; TikTok; Internet/ Google; Memorizing vocabulary; English podcasts; Practice; Social media; book; and Games.